Impacts of Microbial Activity on the Optical and Copper-Binding Properties of Leaf-Litter Leachate - Cuss, Chad; Gueguen, Celine (Frontiers in Microbiology, 2012)
Dissolved organic matter (DOM) is a universal part of all aquatic systems that largely originates with the decay of plant and animal tissue. Its polyelectrolytic and heterogeneous characters make it an effective metal-complexing agent with highly diverse characteristics. Microbes utilize DOM as a source of nutrients and energy and their enzymatic activity may change its composition, thereby altering the bioavailability and toxicity of metals. This study investigated the impacts of microbial inoculation upon the optical and copper-binding properties of freshly-produced leaf-litter leachate over 168 hours. Copper speciation was measured using voltammetry, and using fluorescence quenching analysis of independent fluorophores determined using parallel factor analysis (PARAFAC). Four distinct components were detected. Thirty-five percent of total protein/polyphenol-like fluorescence was removed after 168-hr of exposure to riverine microbes. Using voltammetry, a 6-fold increase in copper-complexing (CC) capacity (130 - 770 μmol Cu/g C) was observed over the exposure period, while the conditional binding constant (log K) decreased from 7.2 to 5.8. Binding parameters were significantly different for all four PARAFAC components and were generally in agreement with voltammetric results in the microbially-degraded samples, but they were significantly different in leachate. These results suggest that non-fluorescent moieties may exert a significant influence upon binding characteristics. Three of four binding sites corresponding to independent PARAFAC components, which had distinct characteristics in the leachate, retained significantly different log K values (p<0.05) after 168 hours of incubation, while their complexing capacities became similar. It was concluded that the microbial metabolization of maple leaf leachate has a significant impact upon DOM composition and its copper-binding characteristics.